Teaching natural sciences: Perspectives of a group of teacher - Aline Juliana Oja Persicheto (Tópicos Educacionais)
The complexity of teaching Natural Sciences at the beginning of children's schooling has promoted discussions, in the sense of favoring the reconfiguration of conceptions about the learning of scientific concepts, as well as the development of pedagogical practices that are more consistent with quality scientific training. This article presents part of a doctoral research that carried out a proposal for shared continuing education, within the scope of the initial years of Elementary School. From the organization of collective meetings at the school, a study group on the teaching of Natural Sciences was structured. The collective meetings held enabled the construction of knowledge that was (re)constructed in a shared way, and the teachers articulated the knowledge acquired during the trajectory of formation and performance with new possibilities, resulting from the collective construction of a reflective work that allowed to qualify the pedagogical practice.